A creative approach to exploring student identity - Bennett, Dawn (The Korean Association for Thinking Development, 2012)
This paper attempts, through a critique of academic discourses about learning, identity and work, to reinforce the need for students to position their learning in relation to creatively exploring the future. This aim is first addressed by way of an overview of the research undertaken thus far, including some of the emergent themes. Then the article presents the context with an overview of work and employment in Australia. This is followed with a discussion of employability and career development. The article concludes by considering what this means for developing self-concept among university students, the potential for possible selves and creativity to play an important role, and the value of incorporating identity development within existing courses.